Intimate partner violence against women. Does violence decrease after the entry of the alleged offender into the criminal justice system? - Paulo Vieira-Pinto; José Ignacio Muñoz-Barús; Tiago Taveira-Gomes; Maria João Vidal-Alves; Teresa Magalhães (Oxford University Press, 2021)
Intimate partner violence (IPV) is simultaneously assumed as a serious crime and a major public health issue, having recurrences as one of its main characteristics and, consequently, re-entries of some alleged offenders in the criminal justice system (CJS). The main goal of this study is to assess if in cases of female victims of IPV, violence decreases after the first entry of the alleged offender in the CJS. A retrospective study was performed based on the analysis of police reports of alleged cases of IPV during a 4-year period. The final sample (n = 1 488) was divided into two groups according to the number of entries in the CJS (single or multiple) followed by a comparative approach. Results suggest that violence decreases after the first entry of alleged offenders in the CJS. Re-entries were found in only 15.5% of the cases but they were accountable for 3.3 times more crimes on average. Besides, victims of recidivism presented more injuries and required more medical care. Thus, a small group of alleged offenders seems to be more violent and accountable for most of the IPV crimes registered in the CJS suggesting that regardless of legal sanctions aiming to deter violence, these measures may not be enough for a certain group of offenders. This study sustains the need for a predictive model to quantify the risk of repeated IPV cases within the Portuguese population.